2023
DOI: 10.1177/17416590221148448
|View full text |Cite
|
Sign up to set email alerts
|

Online sharenting: Identifying existing vulnerabilities and demystifying media reported crime risks

Abstract: Sharenting – the digital sharing of sensitive information of minors by parents or guardians – has not yet been investigated from a criminological perspective. However, there are reported concerns regarding its criminogenic potential amidst fast-growing media interest in sharenting practices, particularly in relation to the perceived crime risks. This article offers an exploratory analysis of cases where such practices led to the victimisation of minors, evidencing the gap between media reports about crime risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In a comparison with other groups analyzed in the ProTechThem project (e.g. Lavorgna et al, 2023), data shows that each community has its own rules and styles to address such consequences and administrators play an important role in orienting and ruling parents toward some essential values and behaviors with the aim to protect children's privacy. Groups' rules provided by administrators are often porous and general, aimed more at ensuring a pleasant affective environment and a useful experience within the group than protect children's privacy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a comparison with other groups analyzed in the ProTechThem project (e.g. Lavorgna et al, 2023), data shows that each community has its own rules and styles to address such consequences and administrators play an important role in orienting and ruling parents toward some essential values and behaviors with the aim to protect children's privacy. Groups' rules provided by administrators are often porous and general, aimed more at ensuring a pleasant affective environment and a useful experience within the group than protect children's privacy.…”
Section: Resultsmentioning
confidence: 99%
“…From a societal perspective, parents are thus considered solely responsible for child rearing, and this legitimates the representation of “bad parenting” as the cause of all social problems (e.g. Gillies, 2008; Lavorgna et al, 2023). The literature shows that social media are spaces in which discourses about good or bad motherhood or mothering practices are performed and constructed (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharing of potentially sensitive information of minors can originate from motivations ranging from parental pride and social isolation, to the search for social influence and profit (Lavorgna et al, 2022). Whilst some of these factors are inherent in the nature of social media platforms (Haillikainen, 2015), some can directly increase the rewards for harmful sharenting practice.…”
Section: Methodsmentioning
confidence: 99%
“…Especially over the last decade, sharenting has received scholarly attention by several disciplines, including law (e.g., Steinberg, 2017; Hancock, 2021), media, communication and cultural studies (e.g., Chalken and Anderson, 2017; Choi and Lewallen, 2018; Archer, 2019; Ranzini et al, 2020; Barnes and Potter, 2021); computer science (e.g., Ammari et al, 2015); educational sciences (e.g., Cino and Damozzi, 2017; Di Bari, 2017; Brosch, 2018); and psychology (e.g., Lazard et al, 2019). So far, however, this common social practice has been almost ignored by criminological scholarship (Lavorgna et al, 2022), which is surprising as we consider that, beyond risks posed by negative psychological repercussions in ignoring children's desire to having (or not) an online identity (Steinberg, 2017) or due to the perpetuation of gender and racial stereotypes (Choi and Lewallen, 2018), there are concerns regarding the potential for financial exploitation (Archer, 2019; Barassi, 2019), grooming and child abuse, cyber hate and identity crimes (e.g., Bezáková et al, 2021; Wachs et al, 2021; Williams-Ceci et al, 2021). Indeed, recent research has shown that, despite the potential under-emerging and underreporting of cases where sharenting has led to the victimisation of minors, there are systemic vulnerabilities in current sharenting practices that can cause the perpetration of harms (Lavorgna et al, 2022).…”
Section: Introductionmentioning
confidence: 99%